PAPR analysis in noncontiguous OFDM systems. Issue 6 (7th November 2016) - Kryszkiewicz, Paweł; Kliks, Adrian; Louet, Yves
Abstract: Noncontiguous orthogonal frequency‐division multiplexing (NC‐OFDM) is a modulation technique suitable for 5G communications. It achieves high spectral efficiency due to aggregation and modulation with nonzero data symbols of only nonoccupied spectrum resources (subcarrier blocks). Similarly as in other multicarrier schemes, one of its main drawbacks is the high variation of instantaneous signal power measured typically by means of peak‐to‐average power ratio (PAPR). Although a lot of research effort has been put in OFDM PAPR characterization, there is a need for such work in the case of NC‐OFDM. This paper finds that PAPR distribution of NC‐OFDM is different than in the case of OFDM. The analysis was done by means of both simulations and analytical derivations. Lower and upper PAPR complementary cumulative distribution function bounds are provided for NC‐OFDM that are much tighter than state‐of‐the‐art solutions. Abstract : Noncontiguous (NC) multicarrier transmission schemes, in both large and small scales, are the promising solutions for efficient use of fragmented spectrum. As for orthogonal frequency‐division multiplexing (OFDM) systems, one of the key problems in NC‐OFDM is the high level of peak‐to‐average power ratio (PAPR) metric. This paper addresses the analysis of the PAPR metric in NC‐OFDM systems, focusing on derivation of analytical formulas for PAPR upper and lower bounds.